2007
DOI: 10.1002/pssb.200642615
|View full text |Cite
|
Sign up to set email alerts
|

Band structure and optical properties of SbSeI: density‐functional calculation

Abstract: PACS 71.15. Mb, 71.20.Nr, 78.20.Ci The electronic structure and linear optical properties of the ferroelectric semiconductor SbSeI are calculated in the nonpolar phase using the density functional methods in the generalized gradient approximation. The obtained electronic band structure shows that SbSeI has an indirect forbidden gap of 1.65 eV. The linear photon-energy-dependent dielectric functions and some optical functions such as absorption and extinction coefficients, refractive index, energy-loss funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Similar to SbSI, SbSeI is ferroelectric and a good photoconductor. [ 14 ] SbSeI has attracted significant attention owing to its important optical and semiconducting properties, which have been applied in X‐ray and γ ‐ray detections as well as optoelectronics. [ 15 ] Based on relativistic quasi‐particle self‐consistent GW theory, Butler et al.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Similar to SbSI, SbSeI is ferroelectric and a good photoconductor. [ 14 ] SbSeI has attracted significant attention owing to its important optical and semiconducting properties, which have been applied in X‐ray and γ ‐ray detections as well as optoelectronics. [ 15 ] Based on relativistic quasi‐particle self‐consistent GW theory, Butler et al.…”
Section: Figurementioning
confidence: 99%
“…Similar to SbSI, SbSeI is ferroelectric and a good photoconductor. [14] SbSeI has attracted significant attention owing to its important optical and semiconducting properties, which have been applied in X-ray and -ray detections as well as optoelectronics. [15] Based on relativistic quasi-particle selfconsistent GW theory, Butler et al reported that SbSeI exhibited a multivalley electronic structure, where several electron and hole basins occurred near the band extrema, which might cause nonconventional photophysical behaviors.…”
mentioning
confidence: 99%
“…The electronic absorption spectra obtained from diffuse-reflectance spectra at room temperature show that SbSeI has an indirect band gap of ∼1.70 eV (Figure 6), which is consistent with the dark-red crystals and in agreement with the previously reported value. 14,18 Several band structure calculations for the room temperature paraelectric phase of SbSeI have been reported based on density functional theory 19 and based on an empirical pseudopotential method. 14b The former study predicts an indirect band gap of 1.65 eV, in which the maximum of the valence band and the minimum of the conduction band are located at the Γ and S symmetry points at the Brillouin zone, respectively.…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…Ambient pressure was shown in the table as 0 kBar. [34] , 1.63 [35] , 1.70 [36] 1.256 [14] , 1.65 [28] , 1.33 [1] In literature review, only ambient pressure studies were found, and no other pressure values were found. Therefore, the data found in other pressure values could not be compared.…”
Section: Resultsmentioning
confidence: 99%